2018
DOI: 10.1007/s00424-018-2234-9
|View full text |Cite
|
Sign up to set email alerts
|

SLC41A1 is essential for magnesium homeostasis in vivo

Abstract: Solute carrier family 41 member A1 (SLC41A1) has been suggested to mediate magnesium (Mg 2+ ) transport by several in vitro studies. However, the physiological function of SLC41A1 remains to be elucidated. In this study, cellular Mg 2+ transport assays combined with zebrafish slc41a1 knockdown experiments were performed to disclose SLC41A1 function and its physiological relevance. The gene slc41a1 is ubiquitously expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“…TRPM7‐mediated Mg 2+ reabsorption is postulated to be regulated by the cyclin and CBS domain divalent metal cation transport mediator 2 (CNNM2) (13). Basolateral extrusion of Mg 2+ is mediated by the solute carrier family 41 member 1 (14). Transcellular Mg 2+ reabsorption in DCT is essential for the maintenance of Mg 2+ homeostasis because DCT is the last nephron segment regulating urinary Mg 2+ excretion and thus fine‐tuning urinary Mg 2+ excretion (15, 16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…TRPM7‐mediated Mg 2+ reabsorption is postulated to be regulated by the cyclin and CBS domain divalent metal cation transport mediator 2 (CNNM2) (13). Basolateral extrusion of Mg 2+ is mediated by the solute carrier family 41 member 1 (14). Transcellular Mg 2+ reabsorption in DCT is essential for the maintenance of Mg 2+ homeostasis because DCT is the last nephron segment regulating urinary Mg 2+ excretion and thus fine‐tuning urinary Mg 2+ excretion (15, 16).…”
mentioning
confidence: 99%
“…TRPM7-mediated Mg 2+ reabsorption is postulated to be regulated by the cyclin and CBS domain divalent metal cation transport mediator 2 (CNNM2) (13). Basolateral extrusion of Mg 2+ is mediated by the solute carrier family 41 member 1 (14). Transcellular Mg 2+ reabsorption in DCT is essential for the maintenance of Mg 2+ homeostasis because DCT is the last nephron segment regulating urinary ABBREVIATIONS: 2-APB, 2-aminoethyl diphenyl borinate; CD, collecting duct; CNT, connecting tubule; CRISPR/Cas9, clustered regularly interspaced short palindromic repeat; DCT, distal convoluted tubule; FSS, fluid shear stress; PKD, polycystic kidney disease; PT, proximal tubule; qPCR, quantitative PCR; sgRNA, single guide RNA; TRPM, transient receptor potential cation channel subfamily melastatin; WT, wild type Mg 2+ excretion and thus fine-tuning urinary Mg 2+ excretion (15,16).…”
mentioning
confidence: 99%
“…Another possibility is that embryo medium provides an essential component, such as Ca 2+ or Mg 2+ , which may provide an important supplement for hepatocellular function. Indeed, hypomagnesemia results in many disorders, including fatigue, seizures and muscle cramps [40]. Zebrafish primarily obtain their intake of magnesium from absorption through the water [40].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, hypomagnesemia results in many disorders, including fatigue, seizures and muscle cramps [40]. Zebrafish primarily obtain their intake of magnesium from absorption through the water [40]. Additionally, other studies have shown that zebrafish larvae body length are positively correlated with bioavailability of calcium and magnesium in the rearing medium [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation